Self-esteem and visual self-presentation on facebook among Chinese undergraduate in a public university in Malaysia - Hui, Michelle Tiong Wen; Lee, Yok Fee (Human Resource Management Academic Research Society, 2021)
Increasing usage of technologies and internet contributes to an introduction of online social networking sites or social media such as Facebook. Facebook has become a platform for self-presentation, especially among the youth. This qualitative study was carried out to study description of self-esteem and visual self-presentation among Chinese undergraduate students in a public university in Malaysia. Altogether ten Chinese students from the university were recruited through purposive sampling and interviewed. This study found that high self-esteem students expressed that they are not addicted to Facebook, accept more real-life/known friends and would not “un-tag” unflattering photographs, while low self-esteem students are addicted to Facebook, accept more strangers on Facebook and would “un-tag”, hide or even delete the unflattering photographs on their Facebook. This study also discovered that management of students’ visual self-presentation on Facebook could be divided into two categories, i.e. selective visual self-presentation and authentic visual self-presentation. In short, this study gave a big pictures on characteristics of self-esteem, types of visual self-presentation, and reasons for using different types of visual self-presentation besides raising awareness of Facebook addiction among university students.